Analisis Karakteristik Marshall Campuran Aspal Modifikasi pada Asphalt Concrete – Wearing Course (AC – WC) dengan Penambahan Serbuk Ban Kendaraan - Manda Tri Putra; Henggar Risa Destania; Febryandi Febryandi (Universitas Kristen Maranatha, 2023)
Roads are the infrastructure that sustains the growth of the economy and plays a very important role in the progress and development of a region. Asphalt functions as a binder in asphalt mixes, making it important to maintain its stickiness, softness, and pliability. Adding additives to asphalt is an alternative that can be used to maintain or increase the grip, soft point, and flexibility of the asphalt. Used motor vehicle tires are made from a variety of materials such as natural rubber, neoprene, chemicals, carbon black and certain oils. The characteristic of rubber is that it is durable and flexible or elastic. This study aimed to determine the value of Optimum Asphalt Content (KAO) in AC-WC mix using modified bitumen with wheel powder with 1% and 2% variations. The results of this study show the results of parametric data analysis for each KAO that the optimum value of the 3 KAOs is 6.18% with the addition of 1% asphalt + rubber tire powder. The parameter values are VIM 4.61%, VMA 18.52%, VFA 75.31%, Stability 1459 kg, and Flow 2.95 mm.